ARBUSCULAR MYCORRHIZAL FUNGAL COMMUNITY STRUCTURE IN A MANIPULATED PRAIRIE AND THE IMPACT ON PLANT COMPETITION - Henning, Jeremiah A. (My University, 2009)
The North American tallgrass prairie once stood the continent?s largest ecosystem. The magnitude of this grassland has been significantly reduced via sustained agriculture. Contemporary ecologists are striving to restore these lost habitats with limited success. Within their roots, many prairie plants harbor symbiotic fungi called arbuscular mycorrhizal fungi. The fungi assist the plants in nutrient acquisition in return for carbohydrates as a food source. Mycorrhizal fungal sporulation was examined in an 8.1-ha reconstructed prairie in Eau Claire County, Wisconsin. In the fall of 2003, the site was planted with differing combinations of native prairie species. It was hypothesized that diverse plant seeding mixtures would promote mycorrhizal fungal diversity. To further test the interaction between plant and fungal communities, each plot was subdivided and treated with the fungicide, chlorothalonil, to suppress mycorrhizal fungi or ammonium nitrate fertilizer, to mimic common agricultural practices. Fungal sporulation within the subplots was impacted by both fungicide and fertilizer treatments. Suppression of mycorrhizal fungi also caused changes in the relative abundance of grasses in the plant community. Based on this observation, two greenhouse experiments were conducted to address the role of mycorrhizal fungi in the competitive ability of two native prairie grasses (Sorghastrum nutans and Andropogon gerardii). The first experiment assessed plant competition by growing the two plant species in a pair-wise combination while suppressing mycorrhizal fungi with fungicide. In the second experiment, plants were inoculated with known mycorrhizal fungal communities in sterilized soil. Mycorrhizal fungi impacted the competitive ability of the grasses as well as the overall root architecture of both species. The results reinforce the importance of mycorrhizal fungi in the structuring, stability and productivity of plant communities. Successful restoration of lost prairie habitats will have to account for its underground fungal symbionts.
A Thesis Submitted in Partial Fulfillment of the Requirements For the Degree of Master of Science-Biology
Keywords: Resilience ecology; Ecosystem health; Prairie restoration; Plant-fungus relationships; Vesicular-arbuscular mycorrhizas